Production of an amylase-degrading raw starch by Gibberella pulicaris - Marlida, Yetti; Saari, Nazamid; Radu, Son; Abu Bakar, Fatimah (2000)
An endophytic fungus, Gibberella pulicaris, produced an amylase which degraded raw starches from cereals and other crops including raw potato, sago, tapioca, corn, wheat and rice starch. In each case, glucose was the main product. Among the raw starches used, raw potato starch gave the highest enzyme activity (85 units mg-1 protein) and raw wheat starch the lowest (49 units mg-1 protein). The highest amylase production (260 units mg-1 protein) was achieved when the concentration of raw potato starch was increased to 60 g l-1. Optimum hydrolysis was at 40 °C and pH 5.5.